(3ceGd GdaQMI aj OaY GdSehe hMaX GdUMIs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s ((3CHh GdaVd eMeO GdCYQL s)
(3ChdgG (B:s
(3GdMeO ddg GdeOHQ GdMcje , Pi GdbhI hGdSdWGf , GdOGFe GdHGbi hcd ef YdjgG aGf , GdPi CNQL GdEfSGf s
(3BNQgG (B:s
(3aWdHJ efg GdCeGf , hMbbJ dg GdbUg , aCMSf EdjgG hCNQLgG Je HMeO Gddg s
(3Cdag hQaYg dNRGfI GdSdWGf GdCTQa CHj GdfUQ bGfUhg GdZhQis
(3hgh ebSe Edi YTQI CHhGHs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs